Safety Summary of the Selective Cytopheretic Device: A Review of Safety Data Across Multiple Clinical Trials in ICU Patients With Acute Kidney Injury and Multiple Organ Failure - H. David Humes, MD; Stuart L. Goldstein, MD; Lenar T. Yessayan, MD; David A. Catanzaro, PharmD; Emily C. Scribe, PharmD; Sai Prasad N. Iyer, PhD; Kevin K. Chung, MD (Critical Care Explorations, 2023)
OBJECTIVES:. Acute kidney injury (AKI) requiring continuous kidney replacement therapy is a significant complication in ICU patients with mortality rates exceeding 50%. A dysregulated immune response can lead to systemic inflammation caused by hyperactivity of pro-inflammatory neutrophils and monocytes leading to tissue damage. The selective cytopheretic device (SCD) is an investigational medical device in a new class of cell-directed extracorporeal therapies distinct from cytokine adsorbers or filters, as it targets activated leukocytes. These leukocytes are the cellular sources driving this hyperinflammatory process. The objective of this report is to summarize the safety experience from clinical studies of the SCD in ICU patients with AKI or acute respiratory distress syndrome (ARDS) and multiple organ dysfunction (MOD). DATA SOURCES AND STUDY SELECTION:. The studies included in this report represent all relevant trials of the SCD conducted in patients with AKI or ARDS and MOD. Adverse event data, clinical laboratory data and mortality rates were described and summarized in this report. DATA EXTRACTION AND DATA SYNTHESIS:. Five clinical studies were included in this report, including four adult studies of AKI and/or ARDS and one pediatric AKI study, which involved 151 patients treated with the SCD in an ICU setting. Over 800 SCD sessions were deployed with an estimated 19,000 exposure hours with no device-related infections or attributable serious adverse events. Furthermore, there were no safety signals of leukopenia, thrombocytopenia, or other indications of immunodepletion or immunosuppression. CONCLUSIONS:. The SCD has shown to be a promising extracorporeal therapy with promising clinical results and a favorable safety profile. These studies support that the SCD can be added as a therapeutic intervention in critically ill AKI patient populations with multiple organ failure without adding additional safety risks.